OnabotulinumtoxinA in the treatment of neurogenic bladder - Gulamhusein A (Dove Medical Press, 2012)
Aziz Gulamhusein, Altaf MangeraDepartment of Urology Research, Sheffield Teaching Hospitals NHS Trust, Royal Hallamshire Hospital, Sheffield, United KingdomAbstract: This review examines the evidence for use of onabotulinumtoxinA in the treatment of neurogenic lower urinary tract dysfunction. Since its first use in 1988 to treat detrusor sphincter dyssynergia, use of botulinum toxin has increased in this group of patients. We discuss the mechanism of action, patient selection, dosing, efficacy, and side effect profile of this now licensed treatment option.Keywords: neurogenic bladder, botulinum toxin, onabotulinumtoxinA, neurogenic detrusor overactivity, detrusor sphincter dyssynergia